ANALISIS JUMLAH CEMARAN MIKROBA DAN IDENTIFIKASI Salmonella sp. DAN Escherichia coli PADA DAGING AYAM DI BEBERAPA TEMPAT PEMASARAN WILAYAH KOTA KUPANG - Ariesthi, Kadek D.; Aspatria, Utma; Talahatu, Anna H. (Jurnal Pangan Gizi dan Kesehatan, 2011)
Meat as a food is a good source of nutrition and prospective. However the meat is very easily damaged if contaminated microbe and will cause poisoning (foodborne diseases) if contaminated pathogen such as Salmonella sp. and Escherichia coli. This research was aimed to analyze the quantity of microbe contamination and identify of Salmonella sp. and Escherichia coli in chicken meat in several marketing areas of Kupang city. While the particular aim is to (1) analyze the quantity of microbe contamination in chicken meat was sold in several marketing areas of Kupang city, (2) identifying the bacteria Salmonella sp. in chicken meat sold in market of Kupang city, (3) identifying bacteria Escherichia coli in chicken meat was sold in market of Kupang city, and (4) to find out the quantity of microbe contamination in chicken meat was sold in three marketing areas. The research design is cross-sectional study using average test to know the differences in the samples, where samples were taken from 3 places of chicken meat market such as Oeba Market, Oebobo Market and Naikoten Market. The data analyse are using a colony counter, anova and the identification.